2022
DOI: 10.1155/2022/4259471
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of Lumbar Spine MRI Images Based on Improved Attention U-Net

Abstract: Lumbar spine segmentation is important to help doctors diagnose lumbar disc herniation (LDH) and patients’ rehabilitation treatment. In order to accurately segment the lumbar spine, a lumbar spine image segmentation algorithm based on improved Attention U-Net is proposed. The algorithm is based on Attention U-Net, the attention module based on multilevel feature map fusion is adopted, two residual modules are introduced instead of the original convolution blocks. a hybrid loss function is used for prediction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…A previous study reported the attention gates in Attention U-net improve the sensitivity and accuracy for dense label predictions by suppressing feature activations in irrelevant regions 20 . Another study on lumbar spine MRI reported that the use of Attention U-net increased the accuracy of lumbar spine segmentation 27 . Similar to previous studies, our study showed that the fractured vertebral body and the BA segmentation results of the Attention U-net were superior to those of the traditional U-net.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the attention gates in Attention U-net improve the sensitivity and accuracy for dense label predictions by suppressing feature activations in irrelevant regions 20 . Another study on lumbar spine MRI reported that the use of Attention U-net increased the accuracy of lumbar spine segmentation 27 . Similar to previous studies, our study showed that the fractured vertebral body and the BA segmentation results of the Attention U-net were superior to those of the traditional U-net.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of computer vision, the attention mechanism is adopted mainly to achieve better performance through adaptively changing the weights of important features. Attention U‐Net, 31 as a typical network model with an attention mechanism, can improve spine image segmentation performance significantly. In the segmentation of the lumbosacral plexus, the attention mechanism 32 improves the accuracy of the network model.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al [20] proposed an improved Attention U-Net algorithm for lumbar spine image segmentation. The algorithm uses attention-based fusion and residual modules to improve performance.…”
Section: Related Workmentioning
confidence: 99%
“…The hyperparameters shown in table I were used for the task of detecting and segmentating vertebrae in lumbar spine MRI images. The use of a large batch size (20) and a large number of workers (8) helps to improve the training efficiency of the model. The use of a constant learning rate (0.01) throughout the training process helps to prevent the model from overfitting the training data.…”
Section: Training Detection and Segmentationmentioning
confidence: 99%